Hypervalent Iodine Mediated C–C Double Bond Activation: A Cascade Access to α-Keto Diacetates from Readily Available Cinnamic Acids - Liu, Le; Zhang-Negrerie, Daisy; Du, Yunfei; Zhao, Kang (Synthesis, 2015)
The reaction of cinnamic acids with (diacetoxyiodo)benzene in 1,2-dichloroethane in the presence of sulfuric acid provides an easy and direct access to the α-keto diacetate framework. This hypervalent iodine mediated oxidative reaction involves a tandem sequence of aryl migration, insertion of an oxygen atom, decarboxylation and diacetoxylation. A reaction mechanism is proposed and discussed in light of control experiments.
Keywords: hypervalent iodine reagents; C–C double bond activation; decarboxylation; aryl migration; α-keto diacetates